1974
DOI: 10.5962/bhl.title.99197
|View full text |Cite
|
Sign up to set email alerts
|

Multipurpose silviculture in ponderosa pine stands of the Montane Zone of central Colorado /

Abstract: Presents silvicultural prescriptions for ponderosa pine in an area where several uses and products of the forest are important but scenic and recreation values predominate. Although far from virgin condition, the pine stands now bear little resemblance to a managed, regulated forest. Present diversity within and between vegetative types can and should be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In the Front Range of Colorado, harvesting done for the purpose of improving tree growth also produces a greater uniformity in density and age structure (Myers 1974;Alexander 1986). The effects of such an approach can be seen on the Black Hills National Forest, where harvesting by industry and firewood cutters has left fewer snags and less downed wood than in unmanaged stands (Lundquist 1995a(Lundquist , 1995b.…”
Section: Timber Harvestmentioning
confidence: 99%
“…In the Front Range of Colorado, harvesting done for the purpose of improving tree growth also produces a greater uniformity in density and age structure (Myers 1974;Alexander 1986). The effects of such an approach can be seen on the Black Hills National Forest, where harvesting by industry and firewood cutters has left fewer snags and less downed wood than in unmanaged stands (Lundquist 1995a(Lundquist , 1995b.…”
Section: Timber Harvestmentioning
confidence: 99%
“…Suppression of wildfires has occurred throughout the 20 th century and most wildfires continue to be suppressed in the region. Because of its proximity to the largest cities in Colorado, the forested montane zone has been one of the most heavily used areas in the state for recreation (Myers 1974).…”
Section: Colorado Front Rangementioning
confidence: 99%
“…Fuel treatments can also be used to control outbreaks of insects and diseases. Heavier thinning targets have been justified in areas severely infested by dwarf mistletoe (Heidmann 1968;Myers 1974) and mountain pine beetle (McCambridge and Stevens 1982). Fuel treatments have been used to increase water yield from watersheds.…”
Section: Other Objectivesmentioning
confidence: 99%
“…Successful regeneration following disturbances is critical to the silviculture and management of these forests. Although successful regeneration of these forests may be possible (Myers 1974, Pearson 1950), more information is needed on the effects of environmental factors on natural regeneration.…”
mentioning
confidence: 99%
“…Hayes (1965) also concluded that inadequate moisture is a common obstacle to regeneration east of the Sierra-Cascades. The time needed for germination and subsequent establishment of ponderosa pine seedlings has been observed to vary with precipitation conditions, both in central Colorado (Myers 1974) and in the southwest (Schubert et al 1970).…”
mentioning
confidence: 99%